Deskripsi Interaksi Sosial Siswa SMA Se-Kota Gorontalo di Masa Pandemi Covid-19 - Firman Taki; Maryam Rahim; Meiske Puluhulawa (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2022)
Abstrak Permasalahan dalam penelitian ini adalah interaksi sosial siswa SMA se-kota Gorontalo di masa pandemi covid-19, sehingga dalam penelitian ini bertujuan untuk mengetahui interaksi sosial siswa SMA se-kota Gorontalo di masa pandemi covid-19. Penelitian ini merupakan penelitian deskriptif kuantitatif yaitu mengkaji interaksi sosial siswa SMA se-kota Gorontalo di masa pandemi covid-19. Populasi dalam penelitian ini adalah siswa SMA se-kota Gorontalo kelas X dengan anggota populasi 1764 siswa yang dijadikan anggota sampel sebanyak 10% atau 209 siswa, teknik pengumpulan data menggunakan angket, data dianalisis dengan menggunakan analisis persentase Berdasarkan hasil penelitian diperoleh data bahwa interaksi sosial siswa SMA se-kota di masa pandemi covid-19 menunjukkan 19,14% pada kategori tinggi, 73,21% pada kategori sedang, 7,66% pada kategori rendah. Rata-rata persentase interaksi sosial SMA se-kota gorontalo di masa pandemi covid-19 67.61%. Dengan demikian interaksi sosial siswa SMA se-kota Gorontalo dikategorikan dalam kategori sedang. Kata Kunci: Interaksi Sosial, Masa Pandemi Covid-19, Siswa ABSTRACT The Problem addressed in this study is the social interaction of senior high school students throughout Gorontalo City during the covid-19 pandemic. Thus, this present study aims to determine the social interaction of senior high school students throughout Gorontalo City during the covid-19 pandemic. This quantitative descriptive study examines the social interactions of senior high school students throughout Gorontalo City during the covid-19 pandemic. Therefore, the population in this study is senior high school students throughout Gorontalo Coty in class X, amounting to 1764 students, with a sampel of 209 students taken from 10% of the population. The data collection technique used in this stdy is questionnaires, while the data analysis is done through percentage analysis. The finding of this study is the social interaction of senior high school students throughout Gorontalo City during the COVID-19 pandemic obtains a perentage of 19.14% in the high category, 73.21% in the medium category, and 7.66% in the lo category. The average percentage of this study is the social interaction of senior high school students throughout Gorontalo City during the covid-19 pandemic is 67.61%. Thus, the social interaction of senior high school students throughout Gorontalo City is included in the medium category. Keywords: Social Interaction, Covid-19 pandemi Period, Students